2015
DOI: 10.1016/j.physletb.2015.09.074
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitating space-times with NUTs

Abstract: We revisit the Taub-NUT solution of the Einstein equations without time periodicity condition, showing that the Misner string is still fully transparent for geodesics. In this case, analytic continuation can be carried out through both horizons leading to a Hausdorff spacetime without a central singularity, and thus geodesically complete. Furthermore, we show that, in spite of the presence of a region containing closed time-like curves, there are no closed causal {\em geodesics}. Thus, some longstanding obstru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
127
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(130 citation statements)
references
References 19 publications
3
127
0
Order By: Relevance
“…As shown by some recent studies [9][10][11], Taub-NUT solution in Lorentzian setup does not lead to serious problems as imagined previously, and when establishing the Smarr relation and first law of thermodynamics, the core ingredient is to introduce a pair of novel conjugate thermodynamic quantities, namely the Misner potential and charge ψ-N [12,16] to ensure that the NUT parameter n varies independently. The thermodynamics of the uncharged Lorentzian Taub-NUT-AdS maintaining the Misner strings present has been formulated, and from the Komar integral notions, it turns out that ψ is actually the surface gravity of the Misner strings and N is interpreted as the integration over it [16].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…As shown by some recent studies [9][10][11], Taub-NUT solution in Lorentzian setup does not lead to serious problems as imagined previously, and when establishing the Smarr relation and first law of thermodynamics, the core ingredient is to introduce a pair of novel conjugate thermodynamic quantities, namely the Misner potential and charge ψ-N [12,16] to ensure that the NUT parameter n varies independently. The thermodynamics of the uncharged Lorentzian Taub-NUT-AdS maintaining the Misner strings present has been formulated, and from the Komar integral notions, it turns out that ψ is actually the surface gravity of the Misner strings and N is interpreted as the integration over it [16].…”
Section: Discussionmentioning
confidence: 89%
“…while the total angular momentum of the spacetime vanishes. According to the line element (9), the Killing vector of the horizon is manifestly given by…”
Section: Geometry Of Charged Taub-nut-ads Spacetimementioning
confidence: 99%
See 1 more Smart Citation
“…In this interpretation, similarly to the infinitely thin, semi-infinite solenoid which generates the Dirac magnetic monopole, the Misner string is a truly physical (singular) material object: a distribution-valued gravimagnetic flux. We have shown that such Misner strings, contrary to previous statements in the literature, are transparent to geodesic motion and that, while they are surrounded by closed timelike curves, these cannot be geodesic [19,20,21]. Adopting this interpretation, a thermodynamics for NUTty black holes was suggested recently in a series of papers [22,23,24,25].…”
Section: Introductionmentioning
confidence: 79%
“…Recently the physical significance of the NUT generalisation of lorenzian black holes solutions in general relativity has been partially rehabilitated, under certain assumptions [25]. Nevertheless there is a open discussion about the physical interpretation of the conical singularities, that may take place in the presence of the NUT parameter.…”
Section: Review Of the Ernst Generating Techniquementioning
confidence: 99%